Classical guitar treasury: duets & ensembles - Noad´s Frederick (Chester Music, 1998)
A unique collection of guitar music wich spans the late Renaissance to the end of the Classical period. Including new and unusual repertoire as well as popular works and showpieces. Suitable for intermediate standard players.